Про механізм конверсії метанолу в формальдегід на Ag-каталізаторі - Бутенко, Анатолій Миколайович; Андрєєв, Герцен Кузьмич; Русінов, Олександр Іванович (НТУ "ХПІ", 2008)
In the presented work is shown that the mechanism parallel flow of oxidizing reactions and simple methanol dehydration (β) is possible only at mole relation (β) oxygen: methanol 0 ˂ β ˂ 0,5. At boundary conditions when β = 0,5, it is possible only oxidizing dehydration of methanol, and at β = 0 – only simple dehydration. These conclusions are confirmed by microscopic level schemes of methanol-to-formaldehyde transformation.
Keywords: окисна конверсія; аргентум; метаналь; дегідрування метанолу; ізотопний обмін